Association between a Functional HLA-G 14-bp Insertion/deletion Polymorphism and Susceptibility to Autoimmune Diseases: A Meta-analysis - Lee, Y H; Bae, S-C (Cellular and Molecular Biology, 2015)
The aim of this study was to determine whether a functional human leukocyte antigen-G (HLA-G) 14-bp insertion (I)/deletion (D) polymorphism is associated with susceptibility to autoimmune diseases. A meta-analysis was conducted to assess the association between an HLA-G 14-bp I/D polymorphism and autoimmune diseases using 1) allele contrast, as well as 2) recessive, 3) dominant, and 4) codominant models. Sixteen articles that included 20 comparative studies with 3,555 patients and 5,225 controls were included in the meta-analysis. These studies were performed on nine Caucasian, six South American, three Asian, one Arab, and one African population samples. Our meta-analysis revealed no association between autoimmune diseases and the HLA-G 14-bp I/D polymorphism [odds ratio (OR) for allele I = 1.055; 95% confidence interval (CI) = 0.963–1.156; p = 0.251)]. However, meta-analysis according to autoimmune disease type revealed an association between systemic lupus erythematosus (SLE) and the II+ID genotype of the HLA-G 14-bp I/D polymorphism (OR = 1.205; 95% CI = 1.036–1.403; p = 0.016). Furthermore, analysis using a codominant model revealed an association between this polymorphism and SLE (OR for ID vs. DD = 1.203; 95% CI = 1.024–1.413; p = 0.024). In contrast, our meta-analysis revealed no association between rheumatoid arthritis (RA), multiple sclerosis (MS), or Crohn’s disease (CD) and the HLA-G 14-bp I/D polymorphism. This meta-analysis showed that the HLA-G 14-bp I/D polymorphism is associated with susceptibility to a subgroup of autoimmune diseases such as SLE, but not RA, MS, or CD. These results support the existence of an association between the HLA-G gene and a subgroup of autoimmune diseases.